Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 75552 by aliesam last updated on 12/Dec/19

Commented by mathmax by abdo last updated on 12/Dec/19

let I =∫_(−(√3)) ^(3(√3))  ∣(x−2)^2 −4∣dx  ⇒I  =∫_(−(√3)) ^(3(√3)) ∣x^2 −4x∣ dx  =∫_(−(√3)) ^(3(√3))  ∣x∣∣x−4∣dx =∫_(−(√3)) ^0 (−x)(4−x)dx+∫_0 ^(3(√3)) x(x−4)dx  =∫_(−(√3)) ^0 (x^2 −4x)dx +∫_0 ^(3(√3)) (x^2 −4x)dx  =∫_(−(√3)) ^(3(√3)) (x^2 −4x)dx =[(x^3 /3)−2x^2 ]_(−(√3)) ^(3(√3))  =(((3(√3))^3 )/3)−2(3(√3))^2   −(((−(√3))^3 )/3) +2(−(√3))^2   =27(√3)−52 +(√3)+6 =28(√3)−46

letI=333(x2)24dxI=333x24xdx=333x∣∣x4dx=30(x)(4x)dx+033x(x4)dx=30(x24x)dx+033(x24x)dx=333(x24x)dx=[x332x2]333=(33)332(33)2(3)33+2(3)2=27352+3+6=28346

Answered by Kunal12588 last updated on 12/Dec/19

I=∫_(−(√3)) ^( 3(√3)) ∣(x−2)^2 −4∣dx  =∫_(−(√3)) ^( 0) [(x−2)^2 −4]dx−∫_0 ^( 4) [(x−2)^2 −4]dx           +∫_4 ^(3(√3)) [(x−2)^2 −4]dx  =[(1/3)(x−2)^3 −4(x−2)]_(−(√3)) ^0 −[(1/3)(x−2)^3 −4(x−2)]_0 ^4         +[(1/3)(x−2)^3 −4(x−2)]_4 ^(3(√3))   =[(8/3)+8+(1/3)(2+(√3))^3 −(2+(√3))]−[(8/3)−8−(8/3)+8]+[(1/3)(3(√3)−2)^3 −4(3(√3)−2)−(8/3)+8]  pls calculate

I=333(x2)24dx=30[(x2)24]dx04[(x2)24]dx+433[(x2)24]dx=[13(x2)34(x2)]30[13(x2)34(x2)]04+[13(x2)34(x2)]433=[83+8+13(2+3)3(2+3)][83883+8]+[13(332)34(332)83+8]plscalculate

Terms of Service

Privacy Policy

Contact: info@tinkutara.com